Electrochemical Determination of D‐Glucose Using Nortropine‐N‐oxyl under Physiological Conditions. Issue 10 (30th June 2015) - Sato, Katsuhiko; Ono, Tetsuya; Yoshida, Kentaro; Ito, Toshinori; Kashiwagi, Yoshitomo
Abstract Nortropine‐N‐oxyl (NNO) was synthesized in a single step from nortropine. The electrocatalytical activity of NNO was evaluated by cyclic voltammetry in pH7.0 phosphate buffer solution. The anodic peak current for ethanol, isopropanol and glucose was enhanced, showing these alcohols were oxidized by electrocatalytic effect of NNO. On the other hand, TEMPO derivative (4‐hydroxy‐2, 2, 6, 6, ‐terramethylpiperidine N‐oxyl free radical) could not oxidize the alcohols under the same condition. The electrochemical response of the NNO to glucose was investigated. The anodic peak current increased with an increase in the concentration of glucose. A linear response to the glucose concentration ranging from 0.1 to 10 mM was obtained.